Neural signature of food reward processing in bulimic-type eating disorders - Simon, Joe J.; Skunde, Mandy; Walther, Stephan; Bendszus, Martin; Herzog, Wolfgang; Friederich, Hans-Christoph (Social cognitive and affective neuroscience, 2016)
Clinical observations and similarities to addiction suggest heightened reward sensitivity to food in patients with bulimic-type eating (BTE) disorders. Therefore, we investigated the expectation and receipt of food reward compared with monetary reward in patients with BTE. Fifty-six patients with BTE (27 patients with binge eating disorder and 29 with bulimia nervosa) and 55 matched healthy control participants underwent event-related functional magnetic resonance imaging while performing both food and monetary incentive delay tasks. BTE patients exhibited reduced brain activation in the posterior cingulate cortex during the expectation of food and increased activity in the medial orbitofrontal cortex, anterior medial prefrontal cortex and posterior cingulate cortex during the receipt of food reward. These findings were relevant to food because we found no significant group differences related to monetary reward. In the patients, higher brain activity in the medial orbitofrontal cortex during the receipt of food reward was related to higher levels of trait food craving and external eating. BTE patients exhibited increased hedonic processing during the receipt of food reward. These findings corroborate the notion that an altered responsiveness of the reward network to food stimuli is associated with BTE.
Gesehen am 11.01.2018